Role of Efficient Human Resource Management in Managing Diversified Organizations - Minghua, Huang (Frontiers in Psychology, 2022)
As the world has turned into global village, it has brought many challenges for the human resource departments regarding the management of diverse workforce in satisfying the employees and creating a diverse yet safe environment for them that does make them uncomfortable. The current study has investigated the effect of human resource practices on the diversity climate with the mediation of job satisfaction. The data had been collected from the human resource personnel of the multinationals in China with the help of 316 participants. The study had deployed SEM analysis to analyze and measure the effect of training & development along with performance appraisal on the diversity climate. The results of the study had revealed that training and development doesn’t have an impact of diversity climate however, performance appraisal has a strong positive impact. Similarly, the mediating role of job satisfaction has been found to ensure the relationship of training and development and performance appraisal with the diversity climate. This study has suggested certain implications to the HR managers of multinationals to ensure a secure diversity climate for the diverse workforce.